Effect of Tongxinluo on nerve regeneration in mice with diabetic peripheral neuropathy - Li, X.; Zhang, J.; Zhao, W.; Yang, H.; Ma, J.; Qi, Y.; Wu, S. (Cellular and Molecular Biology, 2015)
Diabetic peripheral neuropathy (DPN) is a common complication of diabetes. This study aims to investigate the effects of Tongxinluo on the nerve regeneration in diabetic peripheral neuropathy mice. Forty Specefic Pathogen Free (SPF) male KK/Upj-Ay mice were divided into diabetes group, diabetes with high dose Tongxinluo (4g/kg) (D+H), diabetes with mid dose Tongxinluo (2g/kg) (D+M), and diabetes with low dose Tongxinluo (1g/kg) (D+L) groups. Fasting blood glucose (FPG), heat pain threshold, motor nerve conduction velocity (MNCV), insulin-like growth factor-1 (IGF1), activator protein 1 (c-fos), nerve growth factor (NGF), and basic fibroblast growth factor (BFGF) were measured. Results indicated that FPG of diabetes group was significantly higher than that of control group. Heat pain threshold and MNCV were significantly lowered in diabetes group. Expression levels of IGF1, NGF and BFGF were significantly lower than that of control, whereas c-fos expression was significantly higher than that of control group. Tongxinluo treatment (D+M and D+H) significantly up-regulated heat pain threshold, MNCV, and IGF1, NGF and BFGF expression, but decreased c-fos expresson when compared to that of diabetes group. In conclusion, Tongxinluo can ameliorate diabetic peripheral neuropathy, improve MNCV, and promote nerve regeneration. The underlying mechanism needs to be further elucidated.